Cumulative Live Birth Rates in Women Undergoing Progestin-Primed Ovarian Stimulation Using Medroxyprogesterone Acetate, Dydrogesterone, and Progesterone: A Retrospective Analysis - Wu F; Lin J; Zhang J; Wang X; Huang J; Lin J (Drug Design, Development and Therapy)
Fenglu Wu,1 Jing Lin,2 Jing Zhang,1 Xinggang Wang,1 Jialyu Huang,3 Jiaying Lin1 1Department of Assisted Reproduction, Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Center for Reproductive Medicine, Xinhua Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 3Center for Reproductive Medicine, Jiangxi Key Laboratory of Reproductive Medicine, Jiangxi Maternal and Child Health Hospital, Nanchang Medical College, Nanchang, People’s Republic of ChinaCorrespondence: Jialyu Huang, Center for Reproductive Medicine, Jiangxi Key Laboratory of Reproductive Medicine, Jiangxi Maternal and Child Health Hospital, Nanchang Medical College, Nanchang, People’s Republic of China, Email huangjialv_medicine@foxmail.com Jiaying Lin, Department of Assisted Reproduction, Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China, Email lemon_1114@126.comPurpose: To investigate possible differences in cumulative live birth rates (CLBRs) among three progestins medroxyprogesterone acetate (MPA), dydrogesterone (DYG), and Progesterone within the progestin-primed ovarian stimulation (PPOS) protocol.Patients and Methods: This retrospective study included 21,159 women undergoing one of three ovarian stimulation protocols, hMG + MPA, hMG + DYG, or hMG + Progesterone, between September 2013 and January 2024 in our centre. Patients received oral progestins once daily as per their assigned protocol with human menopausal gonadotropin initiated on menstrual cycle day 3. The primary outcome was the CLBR. Secondary outcomes comprised ovarian stimulation parameters, pregnancy outcomes per embryo transfer, and cumulative outcomes per individual.Results: The CLBR demonstrated no statistically significant differences across the three progestin regimens: MPA (6409/14,930, 42.9%), DYG (1430/3205, 44.6%), and Progesterone (1297/3024, 42.9%; p = 0.203). Kaplan-Meier analysis revealed progressive CLBR accumulation through 5 frozen-thawed embryo transfer (FET) cycles, reaching 87.6%, 95.6%, and 93.7% for MPA, DYG, and Progesterone groups, respectively, with all groups achieving 50% CLBR by the second cycle. Cox regression adjusted for confounders confirmed comparable CLBR trajectories (p > 0.05), while multivariable logistic regression showed no association between progestin type and per-cycle live birth rate (p > 0.05). Notably, the Progesterone group exhibited elevated serum progesterone levels (trigger day: p < 0.05), whereas both DYG and Progesterone groups demonstrated higher LH levels than MPA (p < 0.05).Conclusion: Our findings establish clinical equivalence in cumulative live birth outcomes among MPA, DYG, and Progesterone when implemented within the PPOS framework. This evidence supports protocol flexibility in progestin selection, enabling personalized decisions based on pharmacological characteristics, cost considerations, and patient tolerance.Keywords: cumulative live birth rate, medroxyprogesterone acetate, dydrogesterone, progestin-primed ovarian stimulation, progesterons, frozen embryo transfer